Answers

2014-05-17T21:53:38+05:30
(x + y + z)^2 = x^2 + y^2 + z^2 + 2(xy + yz + zx)
15^2 = 33 + 2(xy + yz + zx)
225 - 33 = 2(xy + zy + zx)
xy + yz + zx = 96
x^3 + y^3 + z^3 - 3xyz = (x + y + z)(x^2 + y^2 + z^2 - xy - yz - zx)
                                 = 15(33 - 96)
                                 = -945

0
2014-05-18T07:53:34+05:30
(X+y+z)^2.  = x^2 + y^2 +z^2+2(xy + yz+ xz)
        15^2         = 33+2(xy+yz+xz)
         225 - 33       = 2(xy+yz+xz)
              192/2. =xy + yz+zx
             96.  = xy+ yz+zx
x^3 + y^3 +z^3 - 3xyz = ( x+ y+ z)(x^2 + y^2 + z^2- xy - zx- xz)
                                       = 15(33-96)
                                       = 15 * -63 = - 945
1 2 1
but is the answer correct ???
Yes.....